SENSITIVITY TEST OF KLEBSIELLA PNEUMONIAE FROM SPUTUM OF SUSPECTED PNEUMONIA PATIENTS TO THE ANTIBIOTIC CIPROFLOXACIN - Salis Irawati; Suliati; Retno Sasongkowati; Juliana Christianingsih (PT Wahana Global Education, 2026)
Pneumonia is a pulmonary infection that may result in moderate to severe sickness across all age groups. The predominant microorganisms responsible for pneumonia are Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Klebsiella pneumoniae, Legionella species, Pseudomonas aeruginosa, and Acinetobacter species. Klebsiella pneumoniae is the bacterium most often responsible for pneumonia relative to other bacteria. This research is to assess the susceptibility of Klebsiella pneumoniae isolated from the sputum of patients suspected of pneumonia to the medication Ciprofloxacin. Sputum samples were collected from patients suspected of pneumonia between May and June 2024 at the Syarifah Ambami Rato Ebu Bangkalan Madura District Hospital, with further analysis conducted at the Surabaya Public Health Laboratory Center. The used methodology is sputum cultivation using aerobic techniques. The study used was a descriptive survey, determined by simple random sampling of 30 samples. The test findings indicated that 1 out of 30 samples (3.3%) exhibited Klebsiella pneumoniae bacteria, generating an inhibition zone of 32 mm, classified as sensitive according to CLSI recommendations. This study recommends that future studies use Klebsiella pneumoniae isolate samples from the sputum of probable pneumonia patients aged 2 to 64 years.